Rancang Bangun Web Service Perpustakaan Universitas Sam Ratulangi - Bramwell A. Kasaedja; Rizal Sengkey; Oktavian A. Lantang (Jurnal Teknik Elektro dan Komputer, 2014)
Abstract - Library now has information that is stored in physical or digital form. Advances in technology are increasingly supporting the development of a modern library. UNSRAT have a Special Service Unit Library in each Faculty. With a lot of information that needs a library data management such as book catalog management, book-lending management and membership management, supported with interesting appearance and easy to understand. Thesis with the title "Design of Web Service Sam Ratulangi University Library" aims to design and develop an integrated system for managing catalogs of books, loan management, and management members. This integrated system will be built using web service. Web services built using the Java programming language with SOAP architecture. End user applications built using the C # programming language in the form of stand-alone applications and web pages. In designing and developing web services UNSRAT library, the author will use software development methodologies Diciplined Agile Delivery (DAD). Keywords: Web services, SOAP, Application Library, Diciplined Agile Delivery Abstrak - Perpustakaan saat ini sudah memiliki informasi yang tersimpan dalam bentuk fisik maupun digital. Kemajuan teknologi semakin mendukung berkembangnya perpustakaan modern. UNSRAT memiliki Unit Pelayanan Khusus Perpustakaan pada masing-masing Fakultas. Dengan informasi yang banyak perlu adanya pengelolaan data perpustakaan berupa pengelolaan katalog buku, pengelolaan peminjaman, dan pengelolaan anggota yang didukung dengan tampilan interface menarik dan mudah dipahami. Skripsi dengan judul â€œRancang Bangun Web Service Perpustakaan Universitas Sam Ratulangiâ€ bertujuan merancang dan mengembangkan sebuah sistem terintegrasi untuk pengelolaan katalog buku, pengelolaan peminjaman, dan pengelolaan anggota. Sistem terintegrasi ini akan dibangun menggunakan web service. Web service dibangun menggunakan bahasa pemrograman Java dengan arsitektur SOAP. Aplikasi end user dibangun menggunakan bahasa pemrograman C# dalam bentuk aplikasi stand alone dan halaman web. Dalam merancang dan mengembangkan web service perpustakaan unsrat, penulis akan menggunakan metodologi pengembangan perangkat lunak Diciplined Agile Delivery (DAD). Kata Kunci: Web service, SOAP, Aplikasi Perpustakaan, Diciplined Agile Delivery Rancang Bangun Web Service Perpustakaan Universitas Sam Ratulangi